Unionism and Non-Union Employee Representation: The Interwar Experience in Canada, Germany, the US and the UK - Patmore, Greg (Journal of Industrial Relations, 2013)
The decline in trade union membership in a number of countries has led to concerns over a ‘representation gap’, where workers are deprived of a voice not only in regard to their workplace grievances, but also in regard to their contributions to productivity and the quality of working life. While a number of alternatives have been raised, including joint consultation and works councils, there are concerns that these alternatives may further weaken union organization by establishing rival forms of organization. This article examines the interwar experience with three types of workplace non-union employee representation in Canada, Germany, the US and the UK. Where management recognizes unions and unions actively ensure that they dominate these representation mechanisms, they can enhance union organization.
Keywords: Employee representation plans; Works councils; representation gap; union organization; works committees